2022
DOI: 10.1038/s41598-022-24557-z
|View full text |Cite
|
Sign up to set email alerts
|

Wave induced coastal flooding along the southwest coast of India during tropical cyclone Tauktae

Abstract: The coastal flood during the tropical cyclone Tauktae, 2021, at Chellanam coast, Kerala, India, has invited wide attention as the wave overtopping severely affected coastal properties and livelihood. We used a combination of WAVEWATCHIII and XBeach to study the coastal inundation during high waves. The effect of low-frequency waves and the rise in the coastal water level due to wave setup caused the inundation at Chellanam, even during low tide with negligible surge height. Wave setup raised the water level at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The land-ocean contrast controls the weather conditions and monsoonal rains that vary with the season. Numerous natural disasters, including landslides, earthquakes, land subsidence, oods, droughts, forest res, and dust storms (Sandholz et al, 2016;Mohanty et al, 2022;Chauhan et al, 2021) are frequently observed during the pre-monsoon (July -September). Cyclones are observed along the east and west coast during the premonsoon (May and June) and post-monsoon (October and November) seasons, devastating the Indian region (Singh et al, 2000Mohanty et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The land-ocean contrast controls the weather conditions and monsoonal rains that vary with the season. Numerous natural disasters, including landslides, earthquakes, land subsidence, oods, droughts, forest res, and dust storms (Sandholz et al, 2016;Mohanty et al, 2022;Chauhan et al, 2021) are frequently observed during the pre-monsoon (July -September). Cyclones are observed along the east and west coast during the premonsoon (May and June) and post-monsoon (October and November) seasons, devastating the Indian region (Singh et al, 2000Mohanty et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous natural disasters, including landslides, earthquakes, land subsidence, oods, droughts, forest res, and dust storms (Sandholz et al, 2016;Mohanty et al, 2022;Chauhan et al, 2021) are frequently observed during the pre-monsoon (July -September). Cyclones are observed along the east and west coast during the premonsoon (May and June) and post-monsoon (October and November) seasons, devastating the Indian region (Singh et al, 2000Mohanty et al, 2022). Natural disasters drastically affect life, properties, ecosystems, and infrastructure (Kennish, 2019; Ramakrishnan et al, 2022;Sarkar et al, 2019) in disaster-prone areas.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The capacity of ring roads decays over time due to various aging phenomena such as loads by hit sea waves. The damage to the coast has been identified by Ramakrishnan et al, [1] in their research on wave-induced coastal flooding along the southwest coast of India during tropical cyclone Tauktae. Irham et al, [2] proposed the management of coastal Aceh Province to maintain coastal zones, coastal development, and future environmental challenges.…”
Section: Introductionmentioning
confidence: 95%